Platelets in Wound Healing: What Happens in Space? - Laura Locatelli; Alessandra Colciago; Sara Castiglioni; Jeanette A. Maier; Jeanette A. Maier (Frontiers in Bioengineering and Biotechnology, 2021)
Beyond their fundamental role in hemostasis, platelets importantly contribute to other processes aimed at maintaining homeostasis. Indeed, platelets are a natural source of growth factors and also release many other substances—such as fibronectin, vitronectin, sphingosine 1-phosphate—that are important in maintaining healthy tissues, and ensuring regeneration and repair. Despite rare thrombotic events have been documented in astronauts, some in vivo and in vitro studies demonstrate that microgravity affects platelet’s number and function, thus increasing the risk of hemorrhages and contributing to retard wound healing. Here we provide an overview about events linking platelets to the impairment of wound healing in space, also considering, besides weightlessness, exposure to radiation and psychological stress. In the end we discuss the possibility of utilizing platelet rich plasma as a tool to treat skin injuries eventually occurring during space missions.